1999
DOI: 10.1007/s005920050155
|View full text |Cite
|
Sign up to set email alerts
|

Relation of fetal growth to maternal responses to oral glucose tolerance test throughout gestation

Abstract: Fetal growth is dependent on transplacental supply of fuels. We aimed to assess the effect of serial changes in maternal glucose tolerance and insulin secretion with advancing pregnancy on maternal-fetal outcomes. Sixty-nine healthy pregnant women were studied over the course of gestation for glucose tolerance, by oral glucose tolerance test (OGTT), and hemoglobin A(1c) (HbA(1c)), fetal intrauterine growth (by ultrasound) and pregnancy outcome. Seven women had an abnormal OGTT in the third trimester developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In keeping with other studies (15)(16)(17)(18), we demonstrated maternal glycemia within the normal range was correlated with parameters of fetal growth at birth, including weight, length, and BMI. This effect is most pronounced in the mothers in the upper tertile of glycemic values, suggesting the macrosomia seen in pregnancies complicated by type 2, or gestational, diabetes may be a continuum of the effect of "normal" glucose on birth weight in the nondiabetic pregnancy.…”
Section: Multiple Linear Regression Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…In keeping with other studies (15)(16)(17)(18), we demonstrated maternal glycemia within the normal range was correlated with parameters of fetal growth at birth, including weight, length, and BMI. This effect is most pronounced in the mothers in the upper tertile of glycemic values, suggesting the macrosomia seen in pregnancies complicated by type 2, or gestational, diabetes may be a continuum of the effect of "normal" glucose on birth weight in the nondiabetic pregnancy.…”
Section: Multiple Linear Regression Analysissupporting
confidence: 91%
“…Insulin-mediated growth of the fetus reflects maternal glycemia, with birth weight being increased in diabetic pregnancies, and correlates with maternal glycemia, in both fasting and stimulated levels, in the nondiabetic pregnancy (15)(16)(17)(18). The impact of glycemia within the normal range on early postnatal growth in European Caucasians is uncertain.…”
mentioning
confidence: 99%
“…Some studies have reported that additional testing for GDM in the third trimester may diagnose late GDM that developed de novo, following a negative second-trimester screening. 7,8 However, the evidence is inconsistent regarding the impact of such late GDM diagnosis on perinatal outcomes. Although some studies have described similar outcomes in women with late GDM and controls, others have reported increased risks of macrosomia 9 and cesarean delivery 10 in late GDM pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…This period has been established as optimal for screening because of the increase in insulin resistance in the second trimester. Some studies have reported that additional testing for GDM in the third trimester may diagnose late GDM that developed de novo, following a negative second‐trimester screening 7,8 . However, the evidence is inconsistent regarding the impact of such late GDM diagnosis on perinatal outcomes.…”
Section: Introductionmentioning
confidence: 99%